Glass plate for information recording medium
A high-modulus, low-density glass plate with a glass transition temperature of 700°C or higher addresses substrate deflection and resonance issues, enabling high-capacity and reliable information recording media.
Patent Information
- Application Number
- JP2023113103
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
Current glass substrates for information recording media, such as HDDs, face challenges in achieving high recording capacity due to limitations in reducing the flying height of the magnetic head, caused by substrate deflection and resonance at high rotation speeds, and require improved Young's modulus and heat resistance for high-temperature processing.
A glass plate with a Young's modulus of 94 GPa or more, specific gravity of 2.8 or less, and a glass transition temperature of 700°C or higher, composed of specific glass compositions that balance properties for high rigidity, low weight, and heat resistance, is developed.
The glass plate effectively reduces substrate deflection and resonance, supports high-capacity recording, and withstands high-temperature processing, enhancing the performance and reliability of information recording devices.
Smart Images

Figure 2025010844000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass plate for an information recording medium, specifically to a glass plate suitable for an information recording medium to be used in an information recording device such as an HDD (Hard Disk Drive). [Background technology]
[0002] For information recording devices such as magnetic disks, typified by HDDs, there is a continuing demand for increased recording capacity and reduced access time. One of the means of achieving this is to increase the rotation speed of the information recording medium. However, since the substrate of the information recording medium is bent by rotation, there is a concern that the resonance of the information recording medium increases as the rotation speed increases, and the information recording medium and the magnetic head may eventually collide, causing a reading error or a magnetic head crash. Therefore, with the current substrate, the distance between the magnetic head and the information recording medium, called the flying height, cannot be reduced to a certain level, which is an obstacle to increasing the recording capacity. In order to reduce the bending and resonance of the substrate, it is desirable for the substrate to have a high Young's modulus. Although it depends on the composition, glass is known to have a higher Young's modulus than the aluminum alloy that constitutes the aluminum substrate. A glass plate developed for use as a substrate for an information recording medium is disclosed in, for example, Patent Document 1.
[0003] Furthermore, in the manufacturing process of information recording media, high-temperature processing may be required in the step of forming the recording layer, so the substrate of the information recording medium is required to have heat resistance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2012 / 131824 Summary of the Invention [Problem to be solved by the invention]
[0005] The Young's modulus of the glass plate disclosed in Patent Document 1 is about 80 GPa or less, and there is room for improvement. Therefore, an object of the present invention is to provide a glass plate suitable for information recording media. [Means for solving the problem]
[0006] The present invention relates to Young's modulus is 94 GPa or more, The specific gravity is 2.8 or less, Provided is a glass plate for information recording media, which has a glass transition temperature of 700° C. or higher. Effect of the Invention
[0007] According to the present invention, a glass plate suitable for an information recording medium is provided. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a partial cross-sectional view showing an example of an HDD. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below, but the following description is not intended to limit the present invention to a specific embodiment. In this specification, "substantially free of" a certain component means that the content of the component is less than 0.1 mol%, preferably less than 0.08 mol%, and more preferably less than 0.05 mol%. In the following, the temperature at which the logarithm (log η) of the liquidus viscosity η (unit: dPa s) of the melt of the glass composition becomes n may be expressed as Tn. In the following, the content and the upper and lower limits of the properties can be arbitrarily combined.
[0010] The present invention provides a glass plate for an information recording medium having the following configuration. The glass plate of the first embodiment has a Young's modulus of 94 GPa or more, a specific gravity of 2.8 or less, and a glass transition temperature of 700° C. or more.
[0011] The glass plate of the second embodiment is the glass plate of the first embodiment, which contains a glass composition containing 15 to 30 mol % of MgO.
[0012] The glass plate of the third embodiment is the glass plate of the first or second embodiment, which has a glass transition temperature of 800° C. or higher.
[0013] The glass plate of a fourth embodiment has a Young's modulus of 100 GPa or more in any one of the first to third embodiments.
[0014] The glass plate of a fifth embodiment has any one of the first to fourth embodiments, in which ΔT, calculated by subtracting the devitrification temperature from the liquidus temperature (T2), is 20° C. or higher.
[0015] The glass plate of a sixth embodiment has a specific modulus of elasticity of 36 MNm / kg or more in any one of the first to fifth embodiments.
[0016] The glass plate of a seventh embodiment is the glass plate of any one of the first to sixth embodiments, wherein the specific gravity is 2.65 or less.
[0017] The glass plate of an eighth embodiment is the glass plate of any one of the first to seventh embodiments, and has a thickness of 1 mm or less.
[0018] The glass plate of a ninth aspect is any one of the first to eighth aspects, wherein the difference in SnO2 concentration between the first main surface and the second main surface is 0.5 mass % or less.
[0019] [Hard Disk (HDD)] The glass plate according to the present embodiment has a high Young's modulus and a low specific gravity, and is suitable for use as an information recording medium in an information recording device, particularly in an HDD. FIG. 1 is a partial cross-sectional view of an example of an HDD. The HDD 10 includes a shroud constituting a sealed case, and a plurality of platters 1 arranged in the shroud. In FIG. 1, only a portion of the shroud is shown. The number of platters 1, which are information recording media, is not limited to the four shown in the figure. Each platter 1 includes a glass plate and a magnetic recording layer formed on both main surfaces of the glass plate. Each platter 1 is a ring-shaped disk having a circular hole in the center. A ring-shaped spacer 2 is arranged between adjacent platters 1 to ensure a predetermined interval. The four platters 1 are rotatably supported by a spindle motor 3 at the hole. A head assembly 5 is further arranged in the shroud. The head assembly 5 includes a main body portion arranged on the outer periphery of the four platters 1, and a swing arm portion extending from the main body portion along the main surfaces of the platters 1. The swing arm is equipped at its tip with a magnetic head 6, also called a slider. The magnetic heads 6 are arranged on both main surfaces of the platter 1 in a number corresponding to the number of magnetic heads 6, i.e., eight in FIG. 1. As the platter 1 rotates, the magnetic heads 6 float slightly above the main surface of the platter. Deflection of the platter 1 can cause the magnetic heads 6 to crash.
[0020] In HDDs, multiple thin platters are arranged in a narrow space to increase capacity. In such a dense arrangement, even a slight deflection of the rotating platter can easily cause a crash of the magnetic head. For this reason, it is desirable for the Young's modulus of the material constituting the platter to be high. In addition, in order to reduce the load on the small motor that rotates the multiple platters, it is desirable for the specific gravity of the material constituting the platter to be small. With the progress of high-capacity HDDs, the importance of low specific gravity as well as high Young's modulus is increasing. Furthermore, from the viewpoint of improving recording density, it is desirable to use a magnetic recording layer that can handle energy-assisted magnetic recording, such as heat-assisted magnetic recording (HAMR). High-temperature heat treatment is required to form a magnetic recording layer that can handle heat-assisted recording. In this case, heat resistance is required for the glass plate, which is the substrate. As the characteristics of the glass plate, it is desirable to consider the glass transition temperature (Tg), which is an index of heat resistance, as well as the Young's modulus and specific gravity.
[0021] [Components of the glass composition contained in the glass plate] In the following, all percentages showing the contents of glass components are mol %, unless otherwise specified. (SiO2) SiO2 is a component that forms a glass skeleton and contributes to improving heat resistance. The content of SiO2 may be in the range of 50 to 70%. The content of SiO2 is preferably 52% or more, more preferably 53% or more, particularly preferably 54% or more, and in some cases may be 56% or more, and even more preferably 57% or more. If the content of SiO2 is too high, the Young's modulus may decrease. Therefore, the content of SiO2 is preferably 69% or less, 67% or less, 65% or less, 62% or less, 61% or less, more preferably 60% or less, particularly preferably 59% or less, and in some cases may be 58% or less, 57.8% or less, and even more preferably 57.5% or less.
[0022] (Al2O3) Al2O3 contributes to maintaining the heat resistance, water resistance, etc. of the glass composition, and is also a component that affects the devitrification temperature, viscosity, etc. The content of Al2O3 may be in the range of 7.5 to 26%. The content of Al2O3 is preferably 9% or more, more preferably 10% or more, particularly preferably 11% or more, and in some cases may be 12% or more, even 14% or more. If the content of Al2O3 is too high, the liquidus temperature may rise significantly, causing inconvenience in production. Therefore, the content of Al2O3 is preferably 24% or less, more preferably 22% or less, and in some cases may be 20% or less, even 19% or less.
[0023] Particularly in consideration of mass production, it is preferable that the devitrification temperature of the glass composition is sufficiently lower than the liquidus temperature. The Al2O3 content suitable for sufficiently lowering the devitrification temperature below the liquidus temperature is 11 to 15%, further 11 to 14%, and particularly 11.5 to 13.5%. As described later, in order to sufficiently lower the devitrification temperature compared to the liquidus temperature, it is preferable to add an appropriate amount of Li2O and / or B2O3. The Al2O3 content of 11 to 15% may also contribute to a decrease in specific gravity. The Al2O3 content suitable for sufficiently increasing the crack resistance load and / or sufficiently increasing the glass transition temperature (Tg) is 15 to 26%, further 16 to 22%, and particularly 17 to 21%.
[0024] <(Al2O3) / (SiO2+Al2O3)> The molar ratio of Al2O3 to the total content of SiO2 and Al2O3 is preferably set in the range of 0.15 to 0.35. This makes it easy to achieve both a high Young's modulus and a not too high liquidus temperature. The molar ratio Al2O3 / (SiO2+Al2O3) may be 0.16 or more, further 0.18 or more, and in some cases 0.20 or more, or 0.30 or less. In a composition containing both B2O3 and Li2O, the molar ratio Al2O3 / (SiO2+Al2O3) suitable for reducing the specific gravity is 0.25 or less.
[0025] (MgO) MgO contributes to the improvement of the Young's modulus and is also a component that affects the devitrification temperature, viscosity, etc. The content of MgO may be in the range of 15 to 30%. The content of MgO is preferably 17% or more, more preferably 18% or more, particularly preferably 20% or more, and in some cases may be 21% or more, even 22% or more. If the content of MgO is too high, the liquidus temperature may increase significantly. Therefore, the content of MgO is preferably 29% or less, and in some cases may be 28% or less, even 27% or less.
[0026] The content of MgO suitable for sufficiently lowering the devitrification temperature below the liquidus temperature is 18 to 30%, more preferably 20 to 28%.
[0027] The content of MgO suitable for sufficiently increasing the crack resistance load is 17 to 30%, more preferably 18 to 26%, particularly preferably 22 to 26%.
[0028] (CaO) CaO is an optional component that contributes to maintaining water resistance, etc. and affects the devitrification temperature, viscosity, etc. The content of CaO may be in the range of 0 to 8%. Adding an appropriate amount of CaO is preferable from the viewpoint of lowering the liquidus temperature. Therefore, it is preferable to add CaO (content exceeding 0%), and the content is preferably 0.1% or more, more preferably 0.12% or more, and in some cases may be 2% or more, even 3% or more. However, too much CaO may lower the Young's modulus. Therefore, the content of CaO is preferably 7% or less, more preferably 5% or less, particularly preferably 4.5% or less, and in some cases may be 4% or less. The content of CaO particularly suitable for improving the Young's modulus and crack resistance load is less than 1%.
[0029] <The total of MgO and CaO> The total content of MgO and CaO may be in the range of 18 to 35%, preferably 20 to 30%.
[0030] <(Al2O3) / (MgO + CaO)> The molar ratio of Al2O3 to the total content of MgO and CaO is preferably set to 1.2 or less, and more preferably less than 1. This makes it easy to achieve both a high Young's modulus and a not too high liquidus temperature. The molar ratio Al2O3 / (MgO+CaO) is preferably 0.3 to 0.9, particularly 0.35 to 0.85, and may be 0.4 to 0.7, or even 0.4 to 0.6 in some cases. The molar ratio Al2O3 / (MgO+CaO) may be 0.3 to 0.5. However, the molar ratio Al2O3 / (MgO+CaO) that is particularly suitable for improving the crack load resistance is 0.5 to 1.0, 0.7 or more and less than 1, further 0.7 to 0.9, and especially 0.8 to 0.9.
[0031] (B2O3) B2O3 is an optional component that forms the skeleton of glass and affects properties such as devitrification temperature and viscosity. The content of B2O3 may be in the range of 0 to 3%. Addition of a small amount of B2O3 may contribute to lowering the devitrification temperature. Addition of a small amount of B2O3 may also contribute to lowering the specific gravity. Therefore, it is preferable to add B2O3 (content exceeds 0%), and the content is preferably 0.1% or more, 0.2% or more, particularly 0.3% or more, and in some cases may be 0.5% or more, or even 0.7% or more. However, too much B2O3 may reduce the Young's modulus. The content of B2O3 is preferably 2.5% or less, more preferably 2% or less, particularly preferably 1.8% or less, and in some cases may be 1.6% or less, or even 1.5% or less. One example of a preferable range of the content of B2O3 is 0.1 to 1.6%.
[0032] (LiO) Li2O is a component that modifies the glass skeleton and is an optional component that affects properties such as the liquidus temperature, devitrification temperature, and viscosity. The content of Li2O may be in the range of 0 to 3%. The addition of Li2O within this range is effective in lowering the devitrification temperature. Therefore, it is preferable to add Li2O (content exceeding 0%), and its content is preferably 0.1% or more, 0.2% or more, particularly preferably 0.3% or more, and in some cases may be 0.5% or more, or even 0.7% or more. If the content of Li2O is too high, the Young's modulus may decrease. Therefore, the content of Li2O is preferably 2.5% or less, further preferably 2% or less, particularly preferably 1.8% or less, and in some cases may be 1.6% or less, or even 1.5% or less. An example of the preferred range of the content of Li2O is 0.2 to 2.5%, which is higher than the content of Na2O.
[0033] <Coexistence of B2O3 and Li2O> When B2O3 and Li2O coexist (B2O3 > 0%, Li2O > 0%), it becomes easy to appropriately adjust the liquidus temperature and devitrification temperature of the glass. The coexistence of B2O3 and Li2O is also advantageous from the perspective of reducing the specific gravity of the glass. The total content of B2O3 and Li2O is preferably 0.1% or more, further exceeding 0.5%, particularly preferably 0.7% or more, and in some cases may be 1% or more. Also, this total is preferably 5.5% or less, further preferably 5% or less, particularly preferably 4%, and in some cases may be 3.5% or less. The contents of B2O3 and Li2O may each be 0.1 to 4%, further 0.2 to 3%, particularly 0.2 to 2.5%. From the perspective of reducing the specific gravity, the contents of B2O3 and Li2O may each be 0.1 to 1.3%.
[0034] Adding B2O3 and Li2O in an appropriate ratio is advantageous from the perspective of property improvement. The molar ratio represented by B2O3 / Li2O is preferably in the range of 0.2 to 5, further 0.4 to 2.5, particularly 0.5 to 2, and in some cases may be in the range of 0.8 to 1.25.
[0035] (Na2O) Like Li2O, Na2O is an optional component that affects properties such as liquidus temperature, devitrification temperature, and viscosity. However, since it has a greater effect of lowering Young's modulus than Li2O, its content may be 0 to 0.2%. It is basically desirable not to include Na2O, but it is preferable to add Na2O in an amount of, for example, more than 0% and less than 0.1%, with a limit of 0.2%, or even 0.15%, in order to clarify the glass melt.
[0036] <Total of the ingredients explained above> The total content of the seven components (SiO2, Al2O3, MgO, CaO, B2O3, Li2O, and Na2O) described above is preferably 95% or more, further 97% or more, particularly 98% or more, and especially 99% or more, and may be more than 99.5% or even 99.9% in some cases, or may be 100%. In an embodiment in which the total content of the seven components is 100%, in other words, the glass composition is composed only of SiO2, Al2O3, MgO, CaO, B2O3, Li2O, and Na2O.
[0037] <Additional ingredients> Examples of additional components other than the seven components described above include the following. However, the additional components are not limited to the following, and the displayed content of the additional components is also an example.
[0038] (K2O) Like Li2O, K2O is an optional component that affects properties such as the liquidus temperature, devitrification temperature, and viscosity, and has the effect of promoting clarification of the glass melt. However, since K2O has a greater effect of lowering the Young's modulus than Na2O, its content is preferably set in the range of 0 to 0.1%, more preferably 0 to 0.05%, and particularly preferably 0 to 0.03%.
[0039] (SrO) SrO is also an optional component that affects properties such as liquidus temperature, devitrification temperature, and viscosity. However, the addition of SrO may also reduce Young's modulus. Too much SrO may also impair the homogeneity of the glass melt. Therefore, the SrO content is preferably set in the range of 0 to 5%. The SrO content is preferably 3% or less, more preferably 1% or less, particularly preferably 0.5% or less, and especially preferably 0.1% or less. The SrO content is preferably set so that the sum of the SrO content and the CaO content is 8% or less, more preferably 6% or less, particularly preferably 5% or less, and in some cases 4% or less.
[0040] (BaO) BaO is also an optional component that affects properties such as liquidus temperature, devitrification temperature, and viscosity. However, the addition of BaO can significantly reduce Young's modulus. BaO also has a large environmental impact and is a component that affects the working environment. Therefore, it is preferable that BaO is not substantially included.
[0041] (Transition metal oxides, etc.) Oxides of transition elements (Groups 3 to 11 of the periodic table) called transition metal oxides are also permitted as additional components. Examples of transition metal oxides include TiO2, ZrO2, Fe2O3, Y2O3, La2O3, and CeO2. ZnO, an oxide of an element in Group 12, is also permitted as an additional component. Although it is basically desirable to eliminate these oxides, they may be inevitably mixed in as impurities derived from raw materials or manufacturing equipment. Depending on the type of oxide, the addition of a small amount of them may be effective as a clarifier or the like. The content of oxides of elements in Groups 3 to 12, expressed as the total, is preferably 3% or less, more preferably 1% or less, and particularly preferably 0.5% or less, and may be limited to 0.1% or less if necessary. The content of each transition metal oxide is preferably 0.5% or less, particularly preferably 0.3% or less, and especially preferably 0.1% or less.
[0042] The total content of TiO2 and Y2O3 may be 3% or less, or even 2% or less. The content of TiO2 and Y2O3 may be 1% or less, or 0.7% or less, respectively. Reducing the content of these components may be advantageous in terms of production costs. Reducing the content of these components is also advantageous in terms of reducing the specific gravity.
[0043] In this specification, the content of the oxide of a transition element that exists in a glass composition with multiple valences is calculated in terms of the oxide with the largest oxidation number of the metal. For example, iron oxide is usually present in a glass composition as Fe2O3 or FeO. Therefore, iron oxide present as FeO is converted to Fe2O3, and the content of iron oxide (commonly written as "T-Fe2O3") is calculated by adding it to iron oxide present as Fe2O3.
[0044] (Other Ingredients) Examples of additional components other than those mentioned above include SnO2, Sb2O3, Sb2O5, SO3, Cl, and F. These components can act as fining agents. Examples of other additional components include Ga2O3 and P2O5. The content of each of the components exemplified in this column from SnO2 to P2O5 is preferably 0.5% or less, particularly 0.3% or less, and especially 0.1% or less.
[0045] <Examples of preferred forms of glass composition> In one embodiment of the present invention, the glass composition is substantially free of oxides of rare earth elements. In another embodiment of the present invention, the glass composition contains 0-0.5% T-Fe2O3 and is substantially free of oxides of divalent metals except MgO, CaO and FeO. In yet another embodiment of the present invention, the glass composition is substantially free of alkali metal oxides except Li2O and Na2O. In yet another embodiment of the present invention, the glass composition is substantially free of TiO2 and ZrO2. In yet another embodiment of the present invention, the glass composition has a nitride content of 10 wt % or less, and is preferably substantially free of nitrides. In yet another embodiment of the present invention, the glass composition is not crystallized glass. In other words, no diffraction peaks derived from crystals are confirmed by X-ray diffraction.
[0046] In one embodiment of the present invention, the glass composition has a total content of the above-mentioned seven components (SiO2, Al2O3, MgO, CaO, B2O3, Li2O, and Na2O) and five additional components (K2O, SrO, TiO2, ZrO2, and T-Fe2O3) of 99% or more, further 99.5% or more, particularly 99.9% or more, especially 99.95% or more, and in some cases 100%. In this embodiment, the contents of the five additional components are K2O: 0-0.05%, SrO: 0-5%, TiO2: 0-0.1%, ZrO2: 0-0.1%, and T-Fe2O3: 0-0.5%.
[0047] In one embodiment of the present invention, the glass composition has a total content of the above-mentioned seven components (SiO2, Al2O3, MgO, CaO, B2O3, Li2O, and Na2O) and three additional components (K2O, TiO2, and T-Fe2O3) of 99% or more, further 99.5% or more, particularly 99.9% or more, especially 99.95% or more, and in some cases 100%. In this embodiment, the contents of the three additional components are K2O: 0-0.05%, TiO2: 0-0.1%, and T-Fe2O3: 0-0.5%.
[0048] In one embodiment of the present invention, the glass composition comprises: SiO250-70% Al2O3 7.5~26% MgO 15~30% CaO 0~8% B2O30~3% Li2O 0~3% Na2O 0~0.2% Including, The total content of MgO and CaO is in the range of 18 to 35 mol%, The molar ratio calculated as Al2O3 / (MgO+CaO) is 1.2 or less.
[0049] In one embodiment of the present invention, the glass composition comprises: SiO253-60% Al2O311~15% MgO 18~30% CaO 0~5% B2O3 0.2-1.5% Li2O 0.5~2.5% Na2O 0~0.2% Including, The molar ratio calculated by Al2O3 / (MgO+CaO) is 0.3 to 0.5. The total content of MgO and CaO in this glass composition is in the range of 18 to 35%. This embodiment is particularly suitable for adjusting the devitrification temperature to a preferred range in relation to the liquidus temperature and the like.
[0050] In one embodiment of the present invention, the glass composition comprises: SiO253-60% Al2O315~26% MgO 17~30% CaO 0~5% B2O3 0.2-3% Li2O 0.2~1.5% Na2O 0~0.2% Including, The molar ratio calculated by Al2O3 / (MgO+CaO) is 0.5 to 1.0, preferably 0.7 to 0.9. The total content of MgO and CaO in this glass composition is in the range of 18 to 35%. In this embodiment, the content of CaO may be 0 to 4.5%. This embodiment is particularly suitable for improving the crack resistance load.
[0051] In one embodiment of the present invention, the glass composition comprises: SiO256-70% Al2O315~26% MgO 15~26% CaO 0~3% B2O30~3% Li2O 0~3% Na2O 0~0.2% Including, The molar ratio calculated by Al2O3 / (MgO+CaO) is 0.5 to 1.2. This embodiment is particularly suitable for increasing Tg, that is, improving heat resistance.
[0052] [Glass plate characteristics] In information recording devices such as HDDs, it is required to reduce the bending of the information recording medium. For example, in HDDs, as described above, the bending of the rotating platter can cause the magnetic head to come into contact with the platter and crash. In order to reduce the bending, it is desirable that the rigidity of the glass plate constituting the substrate of the platter is high, specifically, that the Young's modulus is high. In addition, it is desirable that the specific gravity of the glass plate constituting the substrate of the platter is low. Reducing the weight of the platter by reducing the specific gravity of the glass plate can contribute to reducing the power consumption of the HDD. The importance of increasing the Young's modulus and decreasing the specific gravity of the glass plate is particularly high in information recording devices with advanced high capacity, such as HDDs with multiple platters. As described above, in relation to the magnetic recording layer corresponding to thermally assisted recording, the importance of increasing the Tg of the glass plate is also high.
[0053] (specific gravity) In one embodiment of the present invention, the specific gravity of the glass plate is 2.8 or less, preferably 2.7 or less, more preferably 2.65 or less, even more preferably 2.64 or less, and particularly preferably 2.63 or less. A glass plate having such a low specific gravity is particularly suitable for an information recording medium. The lower limit of the specific gravity is not particularly limited, but may be 2.5 or more.
[0054] (Young's Modulus) In one embodiment of the present invention, the Young's modulus of the glass plate is 94 GPa or more, 95 GPa or more, 97 GPa or more, 98 GPa or more, further 100 GPa or more, preferably 101 GPa or more, more preferably 103 GPa or more, and in some cases 104 GPa or more. The upper limit of the Young's modulus is not particularly limited, but may be 110 GPa or less, further 107 GPa or less, and in some cases 105 GPa or less. The method for measuring the Young's modulus will be described in the section of the examples. The glass plate with a high Young's modulus is suitable for information recording medium.
[0055] (Specific elastic modulus) The specific elastic modulus can be obtained by dividing the Young's modulus by the specific gravity. A glass plate having a high specific elastic modulus is particularly suitable for an information recording medium. This is because it is desirable that the load on the driving device such as a motor and the like is small and the deflection is small when the information recording medium is rotated at high speed. In one embodiment of the present invention, the specific elastic modulus of the glass plate is 36MNm / kg or more, 36.5MNm / kg or more, preferably 37MNm / kg or more, more preferably 38MNm / kg or more, and particularly preferably 39MNm / kg or more.
[0056] (Crack resistance load) In one embodiment of the present invention, the crack resistance load of the glass plate is 300g or more, preferably 400g or more, more preferably 500g or more. Surprisingly, according to one embodiment of the present invention, it is also possible to provide a glass plate having a particularly high crack resistance load, for example 900g or more, even 1000g or more, particularly 1200g or more. The upper limit of the crack resistance load is not particularly limited, but may be 2000g or less. A method for measuring the crack resistance load will be described in the Examples section. A glass plate having a high crack resistance load is suitable for an information recording medium. In another embodiment of the present invention, the glass plate has a crack resistance load in the range of 300 to 550g and a devitrification temperature TL of 1250 to 1350°C.
[0057] (high temperature viscosity) In one embodiment of the present invention, the temperature T2 of the glass plate (the temperature at which the logarithm (log η) of the liquidus viscosity η (unit: dPa·s) of the melt of the glass plate is 2; the liquidus temperature) may be 1490°C or less, 1480°C or less, further 1470°C or less, and in some cases 1460°C or less. A low T2 is suitable for mass production of information recording media. Similarly, the temperature T2.5 may be 1400°C or less, 1390°C or less, further 1380°C or less, and in some cases 1370°C or less. The temperature T3 may be 1310°C or less, 1300°C or less, further 1290°C or less, and in some cases 1280°C or less.
[0058] (devitrification temperature) In one embodiment of the present invention, the devitrification temperature TL of the glass plate is 1450°C or less, preferably 1400°C or less, more preferably 1380°C or less, and particularly preferably 1350°C or less. Crystals are easily precipitated in glass plates with a high devitrification temperature TL. Crystals precipitated on the surface of an information recording medium such as a platter can cause the smoothness of the medium surface to be impaired. A low devitrification temperature is very important for glass plates for information recording media.
[0059] (Relationship between high temperature viscosity and devitrification temperature) In one embodiment of the present invention, the value (ΔT) obtained by subtracting the devitrification temperature TL of the glass sheet from the liquidus temperature T2 is 20° C. or higher, preferably 30° C. or higher, more preferably 50° C. or higher, and particularly preferably 100° C. or higher.
[0060] (glass transition temperature) In one embodiment of the present invention, the glass plate has a glass transition temperature (glass transition point) Tg of 700°C or higher, more preferably 725°C or higher, more preferably 750°C or higher, and particularly preferably 800°C or higher. A glass composition with a high Tg is particularly suitable for information recording media. As described above, high temperature treatment may be required in the process of forming the recording layer, and in this case, the information recording medium is required to have heat resistance. The upper limit of the glass transition temperature Tg is not particularly limited, but is, for example, 850°C.
[0061] The methods for measuring the liquidus viscosity η, the devitrification temperature TL, and the glass transition temperature Tg will be explained in the Examples section.
[0062] [Information recording media] The glass plate described above is suitable for use as an information recording medium. A glass plate having a high Young's modulus and thus less bending, a small specific gravity and thus less load on a motor, and a high Tg and thus high heat resistance is particularly suitable for an information recording medium. The glass plate may have a disk-like shape. The disk-like glass plate may have a hole in its center. The outer diameter of the glass plate may be 3.5 inches or less, 2.5 inches or less, or even 1.8 inches or less. The thickness of the glass plate may be, for example, 1 mm or less, 0.8 mm or less, 0.7 mm or less, 0.635 mm or less, or even 0.5 mm or less.
[0063] The glass plate may be chemically strengthened glass. As is well known, chemical strengthening is a process in which compressive stress is introduced into the surface of glass by replacing alkali ions contained in glass with alkali ions having a larger ionic radius, for example, lithium ions with sodium ions, or sodium ions with potassium ions. The chemical strengthening process of the glass plate is usually carried out by contacting the glass plate with a molten salt containing alkali ions. Examples of the molten salt include potassium nitrate and a mixed salt of potassium nitrate and sodium nitrate. When using a molten salt of potassium nitrate alone, the temperature of the molten salt is appropriately about 460°C to 500°C, taking into consideration the thermal decomposition of potassium nitrate and the heat resistance of glass. The time for which the glass is contacted with the molten salt is appropriately, for example, 4 hours to 12 hours.
[0064] The surface roughness Ra of the glass plate of this embodiment may be 0.3 nm or less, 0.2 nm or less, or even 0.1 nm or less. To be precise, Ra is the arithmetic mean roughness specified in the Japanese Industrial Standards (JIS) B 0601-2001. The glass plate only needs to have a surface roughness as small as the above on at least one of its main surfaces, and preferably on both of its main surfaces. A glass plate with excellent surface flatness is suitable for an information recording medium.
[0065] As described above, the glass plate of the present embodiment can have a low devitrification temperature TL and / or a large ΔT. Therefore, it is suitable for reducing the surface roughness by polishing. Since crystal grains exist in the glass plate where devitrification has occurred, it is difficult to achieve the above-mentioned level of flatness even if it is precisely polished. The above-mentioned level of reduction in surface roughness can be achieved, for example, by precision polishing using an abrasive containing cerium oxide.
[0066] There is no particular limitation on the method for producing the glass sheet of this embodiment, but a method in which the cooling rate of the glass melt is faster than that of the float method, such as a press molding method, an overflow downdraw method, or a roll-out method, is suitable. This is because the cooling rate is extremely slow in the production by the float method, and devitrification is likely to occur. In a glass sheet obtained by the float method, that is, float glass, diffusion of tin is observed to the bottom surface that contacts the molten tin in the float tank. Since tin does not diffuse to the top surface on the opposite side, a concentration difference of tin oxide is observed between the two main surfaces of the float glass. This concentration difference often reaches about 1 mass% or more. In the glass sheet of this embodiment, the tin oxide (SnO2) concentration difference between the first main surface and the second main surface may be 0.5 mass% or less, or even 0.1 mass% or less. The tin oxide (SnO2) concentration on the main surface can be represented by the maximum concentration of SnO2 when measured near the main surface, specifically, to a depth of 10 μm from the main surface. This maximum concentration can be measured by the method described in the Examples section. EXAMPLES
[0067] The present invention will now be described more specifically with reference to examples. Glass raw materials were prepared to obtain the compositions shown in Tables 1 and 2, and melted for 4 hours in an electric furnace maintained at 1500 to 1600°C. During melting, the glass was stirred several times with a quartz glass stirring rod to ensure the homogeneity of the glass. The molten glass was then poured into a stainless steel frame to produce a plate-shaped glass. The plate-shaped glass was maintained at a temperature of the glass transition temperature of each glass +20 to 50°C for more than 2 hours, and then slowly cooled to room temperature over about 8 hours. The glass thus obtained was subjected to grinding and polishing (cerium oxide polishing) to obtain a sample glass.
[0068] (specific gravity) The specific gravity (density) was measured for a small piece of sample glass by the Archimedes method using water as the immersion liquid.
[0069] (Young's Modulus) The Young's modulus was measured according to the ultrasonic pulse method described in Japanese Industrial Standard (JIS) R 1602 - 1995. Each test piece was a rectangular parallelepiped with dimensions of 5 mm × 25 mm × 35 mm. Also, the measurement was carried out at room temperature in the atmosphere. The device used was model 25DLPlus manufactured by Panametrics. Further, the specific elastic modulus was obtained by dividing the Young's modulus by the specific gravity.
[0070] (Crack resistance load) The crack resistance load was measured by a test in which a Vickers indenter was pressed against the surface of a mirror - polished sample glass. The device used was a Vickers hardness tester manufactured by Akashi Seisakusho. The sample glass was processed into a plate shape with parallel planes. Also, the plane against which the indenter was pressed was polished to a mirror surface using a suspension of cerium oxide polishing agent. The Vickers indenter was pressed against the mirror - polished surface for 15 seconds, and 5 minutes after unloading, it was measured whether cracks occurred from the vertices in the square indentation remaining on the surface of the sample glass. Whether cracks occurred or not was judged by observing using a microscope incorporated in the Vickers hardness tester. The magnification of the microscope was 100 times. This measurement was carried out 10 times, and the crack occurrence probability P was calculated by dividing the number of vertices where cracks occurred by the total number 40 of vertices measured. The above measurement was repeated by changing the load in the order of 50 g, 100 g, 200 g, 300 g, 500 g, 1000 g, 2000 g until P = 100% was reached, and the crack occurrence probability P at each load was obtained. In this way, two adjacent loads WH and WL straddling P = 50% and the crack occurrence probabilities PH and PL at that time (PH < 50% < PL) were obtained. With the load and the crack occurrence probability as the horizontal axis and the vertical axis respectively, a straight line passing through the two points (WH, PH) and (WL, PL) was drawn, and the load at which P = 50% was taken as the crack resistance load.
[0071] (Devitrification temperature TL) The sample glass was crushed, passed through a sieve with a mesh size of 2.380 mm, and the glass particles remaining on a sieve with a mesh size of 1.000 mm were collected. The glass particles were immersed in ethanol, ultrasonically cleaned, and then dried in a thermostatic chamber. 30 to 32 g of the glass particles were placed on a platinum boat with a width of 12 mm, a length of 200 mm, and a depth of 10 mm so that the thickness was almost constant, to prepare a measurement sample. The platinum boat was kept in an electric furnace (temperature gradient furnace) with a temperature gradient of 950 to 1550 °C for 2 hours. The maximum temperature at the site where a crystalline phase (devitrification) distributed in the measurement sample was observed was evaluated as the liquidus temperature TL.
[0072] (T2, T2.5, T3) T2, T2.5, and T3 were measured by measuring the viscosity of the sample glass at each temperature at 25° C. intervals using a platinum ball pulling method, and calculating the intermediate viscosities using the Fulcher formula.
[0073] (glass transition temperature Tg) A cylindrical specimen with a diameter of 5 mm and a length of 18 mm was prepared from the sample glass, and the thermal expansion curve was measured by a TMA device when heated at 5°C / min. The glass transition temperature Tg was obtained based on this curve.
[0074] (SnO2 concentration) Using an electron probe microanalyzer (EPMA; JEOL "JXA8600") and a wavelength dispersive X-ray detector (WDX; accelerating voltage: 15 kV, sample current: 2.5x10-7A, scan speed: 66 μm / min, analyzing crystal: PET) attached to it, divalent and tetravalent Sn present from the surface of the glass plate to a depth of 10 μm was measured and converted to SnO2. The measurement was performed on both main surfaces of the glass plate. The maximum concentration at a depth of 10 μm was taken as the SnO2 concentration on the main surface.
[0075] The above-mentioned characteristics were measured for each sample obtained. The results are shown in Tables 1 and 2. As can be seen from Comparative Examples 3 and 4, it is possible to increase the Young's modulus by adding TiO2, Y2O3, etc. However, as can be seen from Examples 1 to 10, the improvement of the Young's modulus by MgO is advantageous in that it not only improves the Young's modulus but also enables control of the specific gravity. The Young's modulus in Comparative Examples 1 to 2 and 5 to 7 was less than 98 GPa. Comparative Examples 1 and 2 have a relatively high T2, which is somewhat disadvantageous for mass production. When measured using a scanning probe microscope (SPM; "SPI3700" manufactured by SII Nanotechnology), Ra was in the range of 0.01 nm to 0.30 nm for both sides of all Examples and Comparative Examples. In addition, the difference in SnO2 concentration between both main surfaces of the glass plate was 0.1 mass % or less for all Examples and Comparative Examples.
[0076] [Table 1]
[0077] [Table 2]
Claims
1. Young's modulus is 94 GPa or more, The specific gravity is 2.8 or less, A glass plate for an information recording medium, having a glass transition temperature of 700° C. or higher.
2. 2. The glass sheet of claim 1, comprising 15 to 30 mol % MgO.
3. 2. The glass sheet according to claim 1, having a glass transition temperature of 800° C. or higher.
4. 2. The glass plate according to claim 1, having a Young's modulus of 100 GPa or more.
5. The glass plate according to claim 1, wherein ΔT, calculated by subtracting the devitrification temperature from the liquidus temperature (T2), is 20° C. or higher.
6. 2. The glass plate according to claim 1, having a specific elastic modulus of 36 MNm / kg or more.
7. 2. The glass sheet according to claim 1, having a specific gravity of 2.65 or less.
8. 2. The glass sheet of claim 1 having a thickness of 1 mm or less.
9. SnO between the first and second main surfaces 2 2. The glass plate according to claim 1, wherein the concentration difference is 0.5% by mass or less.
Citation Information
Patent Citations
Glass composition suitable for chemical strengthening and chemically strengthened glass article
WO2012131824A1